Design and analysis of algorithms - Smith, Jeffrey Dean, 1951- (Boston : PWS-KENT Pub. Co., 1989)
For junior/senior computer science majors. * Presents concept of the algorithm as a product of design techniques that students are able to master
Includes bibliographical references (p. 429-432) and index.
1
Keywords: Algorithms